1985
DOI: 10.1016/s0140-6736(85)92801-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Viral Infections and Multiple Sclerosis

Abstract: Over an 8 year period, 170 patients with multiple sclerosis (MS) and 134 healthy controls were assessed at monthly intervals in order to ascertain environmental factors which might be important in producing exacerbation or progression of the illness, and to compare the frequency of common viral infections in the two groups. During cumulative periods designated "at risk" (2 weeks before the onset of infection until 5 weeks afterwards) annual exacerbation rates were almost 3-fold greater than those during period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
297
3
6

Year Published

1986
1986
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(323 citation statements)
references
References 8 publications
13
297
3
6
Order By: Relevance
“…Based on these findings we posed the hypothesis that APC-activating agents could disrupt endogenous immunoregulatory processes, thereby allowing tolerized autoreactive T cells to regain their biological functions and mediate autoimmune disease. This concept is intriguing in light of the fact that autoimmune diseases such as MS are more likely to relapse in the setting of infectious illness, which is typically associated with APC activation (22)(23)(24)(25)(26)(27)(28). According to our theory, APCs that bear autoantigenic peptides (or molecular mimics) and are activated by "danger signals" in the course of an infection could mediate the conversion of bystander autoreactive T cells from a tolerized into an effector phenotype.…”
Section: Activation Of Apcsmentioning
confidence: 99%
“…Based on these findings we posed the hypothesis that APC-activating agents could disrupt endogenous immunoregulatory processes, thereby allowing tolerized autoreactive T cells to regain their biological functions and mediate autoimmune disease. This concept is intriguing in light of the fact that autoimmune diseases such as MS are more likely to relapse in the setting of infectious illness, which is typically associated with APC activation (22)(23)(24)(25)(26)(27)(28). According to our theory, APCs that bear autoantigenic peptides (or molecular mimics) and are activated by "danger signals" in the course of an infection could mediate the conversion of bystander autoreactive T cells from a tolerized into an effector phenotype.…”
Section: Activation Of Apcsmentioning
confidence: 99%
“…3,4 Emerging evidence suggests that MS patients exposed to infections have a significantly greater risk of relapse. 3,4 Clinically, it has been shown that a significant number of MS relapses are preceded by a viral infection 5 or bacterial infection. 6,7 However, no simple relationship between these processes has emerged.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is growing evidence that there may be a link between infection and relapse (Buljevac et al, 2002). A number of studies have shown that approximately one-third of MS relapses are preceded by a viral infection (Sibley et al, 1985;Andersen et al, 1993;Panitch, 1994;Edwards et al, 1998;Buljevac et al, 2002). Relapse in individuals with MS has also been associated with bacterial infections, such as those of the urinary tract, which appear to trigger relapse in as many as 30% of MS patients (Rapp et al, 1995).…”
Section: Introductionmentioning
confidence: 99%